2020
DOI: 10.1097/scs.0000000000007223
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Repair Idea on Nasal Sidewall Defect in Asians: Local Tissue Regeneration

Abstract: Background: The traditional ways indicate using different types of flap to repair the nasal sidewall defect, but the scar in the donor area or bloated flap is a problem that cannot be ignored. This study propose the clinical application of the principle of tissue regeneration priority in small defects (defect diameter <1.0 cm) of nasal sidewall. Methods: A retrospective study of 3 patients experienced the tumor excision and tissue regeneration healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The surgical method was the same as previously described and all the operations were done by a single surgeon (G). 9 We marked the incision line about 1 mm away from the edge of the tumor with methylene blue, and the depth was based on the standard of complete resection of the tumor. The principle of tumor resection followed the principle of Mohs surgery, 10 and the resected tumor was examined pathologically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical method was the same as previously described and all the operations were done by a single surgeon (G). 9 We marked the incision line about 1 mm away from the edge of the tumor with methylene blue, and the depth was based on the standard of complete resection of the tumor. The principle of tumor resection followed the principle of Mohs surgery, 10 and the resected tumor was examined pathologically.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that local tissue regeneration can repair nasal sidewall defect with good effect, fewer complications, and easy operations, especially for Asians who are easy to leave incision scars. 9 This method is now extended to repair small soft tissue defects in other parts of the face. The summary report is as follows.…”
mentioning
confidence: 99%